Pore morphology in thermally-treated shales and its implication on CO2 storage applications: A gas sorption, SEM, and small-angle scattering study. (1st January 2023) - Chandra, Debanjan; Bakshi, Tuli; Bahadur, Jitendra; Hazra, Bodhisatwa; Vishal, Vikram; Kumar, Shubham; Sen, Debasis; Singh, T.N.
Highlights: Alteration of shale pore attributes with oxic and anoxic heat treatment. Effect of mineral and organic matter composition of shale on thermal response. Change in shale pore connectivity depending on heating conditions. Enhancement in CO2 storage potential in shale due to thermal treatment. Abstract: A combination of high-resolution imaging, low-pressure gas adsorption, and small-angle X-ray and neutron scattering quantifies changes in the pore characteristics of pulverized shale samples under oxic and anoxic environments up to 300 ℃. Clay-rich early-mature shales have a fair potential to generate hydrocarbons, the total organic carbon content of which lies within a range of 2.9 % to 7.4 %. High-resolution imaging indicates restructuring and coalescence of Type III kerogen-hosted pores due to oxic heating, which causes up to 580 % and 300 % increase in the surface area and pore volume of mesopores respectively. Similarly, up to 300 % and 1200 % increase in micropore surface area and pore volume is observed post oxic heating. However, during anoxic heating, bitumen mobilizes, leads to pore-blockage, and reduces the surface area and pore volume up to 45 % and 12 % respectively without any significant mass loss up to 350 °C. Between 400 and 550 °C, considerable loss in mass occurred due to breaking of organic matter, facilitated by the presence of siderite that caused up to 30 % loss in mass. The test conditions display starkly opposite effects in pores that have a width of < 100 nm when compared to the larger macropore domain, which has a pore width in the range of 100 to 700 nm as inferred from their small-angle X-ray (SAXS) and neutron (SANS) scattering behaviour, respectively. Despite the formation of new mesopores or the creation of new networks of pores with rougher surfaces, the fractal behavior of accessible mesopores in combusted shales minimally increase mesopore surface roughness. The pyrolyzed shales exhibit decreased mesopore surface roughness at higher temperatures, which indicates smoothening of pores due to pore blocking. Increase in pore volume and surface area due to oxic-heat treatment enhances the feasibility of long-term CO2 storage in shales.